Autologous fat transplantation prior to permanent expander implant breast reconstruction enhances the outcome after two years: a randomized controlled trial - Anna Lindegren; Inkeri Schultz; Åsa Edsander-Nord; Jacinth Yan; Marie Wickman (Journal of Plastic Surgery and Hand Surgery)
Radiotherapy is important in breast cancer treatment. A side effect of the treatment is fibrosis that decreases the possibility for a successful breast reconstruction with expanders and with high patient satisfaction with the result. The most common option for mastectomized, irradiated women wishing for a breast reconstruction is autologous tissue transplantation. However, some patients are not suitable for flap surgery. Fifty mastectomized and irradiated women were included in a randomized controlled trial. They underwent breast reconstruction with expanders and were allocated 1:1 to either receive pre-treatment with autologous fat transplantation (AFT) or not. Primary outcomes were frequency of reoperations and complications. Secondary outcomes were number of days in hospital, number of outpatient visits to surgeon or nurse and patient reported outcome as reported with Breast Q. Follow-up time was 2 years. Fifty-two per cent of the intervention group and 68% of the controls underwent reoperations (p = 0.611). Thirty-two per cent of the intervention group and 52% of the controls had complications (p = 0.347). The median number of consultations with the nurse was four in the intervention group and six in the control group (p = 0.002). The AFT patients were significantly more satisfied with their breasts and psychosocial well-being after 2 years. They also had higher increase in satisfaction with breasts, psychosocial well-being, and sexual well-being when comparing baseline with 2 years postoperatively. This randomized controlled trial indicates benefits of AFT prior to breast reconstruction with expanders, especially on patient reported outcome even if the study sample is small.